Derivatives of benzo-1,4-thiazine-3-carboxylic acid and the corresponding amino acid conjugates - Kisszékelyi, Péter; Peňaška, Tibor; Stankovianska, Klára; Mečiarová, Mária; Šebesta, Radovan (Beilstein Journal of Organic Chemistry, 2022)
Herein, we present the synthesis and utilization of derivatives of 4H-benzo[b][1,4]thiazine-3-carboxylic acid. These benzothiazine compounds were assembled via the coupling of aminothiols and bromopyruvates. Oxidative dimerization of these starting materials was also observed and the corresponding benzothiazine dimers were isolated. Moreover, the coupling of benzothiazines with amino acids was realized. In doing so, an enantioselective synthesis of the nonproteinogenic amino acid 2-amino-3-propylhexanoic acid was accomplished.
Keywords: amino acid; benzothiazine; oxidative dimerization; peptide coupling; stereoselective hydrogenation